Pengembangan Metode Pembelajaran Online Berbasis E-learning (Studi Kasus Mata Kuliah Bahasa Pemrograman) - Budi Budi; Brian Nurjayanti (Jurnal Sains Terapan : Wahana Informasi dan Alih Teknologi Pertanian, 2012)
E-learning method provides the ease and smoothness of the teaching-learning process for both students and lecturers. With e-learning methods, teachers can increase the intensity of interactive communication with students outside of official class hours. E-learning methods provide flexibility to the faculty to provide access to students to gain scientific references related to the course that may not be obtained during the hours of lecture and lab activities. These references may be scientific papers, popular articles or electronic journals.   This would be particularly useful for students, because in addition to strengthening the understanding of students for each subject of the course, a reference of the international journals will greatly help to expand the students’knowledge, as well as improve their English. So hopefully in the future, IPB Diploma graduates, especially those who earn Programming Language course, will have high competitiveness in the global competition which is increasingly filled by graduates of foreign universities.Keyword : e-learning, online, course, learning methods.